PTEN promotes intervertebral disc degeneration by regulating nucleus pulposus cell behaviors. (12th November 2019) - Xi, Yongming; Ma, Jinfeng; Chen, Yan
Abstract: Intervertebral disc degeneration (IDD) is induced by multiple factors including increased apoptosis, decreased survival, and reduced extracellular matrix (ECM) synthesis in the nucleus pulposus (NP) cells. The tumor suppressor phosphatase and tensin homolog deleted from chromosome 10 (PTEN) is the only known lipid phosphatase counteracting the PI3K/AKT pathway. Loss of PTEN leads to activated PI3K/AKT signaling, which plays a key role in a variety of cancers. However, the role of PTEN/PI3K/AKT signaling nexus in IDD remains unknown. Here, we report that PTEN is overexpressed in degenerative NP, which correlates with inactivated AKT. Using the PTEN knockdown approach by lentivirus‐mediated short interfering RNA gene transfer technique, we report that PTEN decreases survival but induces apoptosis and senescence of NP cells. PTEN also inhibits expression and production of ECM components including collagen II, aggrecan, and proteoglycan. Furthermore, PTEN modulates the expression of ECM regulatory molecules SOX‐9 and matrix metalloproteinase‐3 (MMP‐3). Using small‐molecule AKT inhibitor GDC‐0068, we confirm that PTEN regulates NP cell behaviors through its direct targeting of PI3K/AKT. These findings demonstrate for the first time that PTEN/PI3K/AKT signaling axis plays an important role in the pathogenesis of IDD. Targeting PTEN using gene therapy may represent a promising therapeutic approach against disc degenerative diseases.